Projects constructed on the Tigris and Euphrates international watercourses and their impacts on Iraqi's water utilization: an international law approach - Hussein, Omar Ahmed (2017)
Water plays a key role in a nation’s economic and social development. The growing interest in water and international rivers among the international community has culminated in the UN adoption of the Convention on the Law of the Non- navigational Uses of International Watercourses 1997. Since the dawn of history, Iraq has always been associated with two large rivers, the Tigris and Euphrates. It is also known as ‘Mesopotamia’ which means the country of two rivers. The oldest civilizations were built on the banks of these two rivers. Iraq was the first country that uses the water from these two rivers and it is still depending on the water from these two rivers in order to achieve both the economic and social development. The aim of this thesis is to examine the negative effects of the projects undertaken by the upstream countries of these two rivers on Iraq’s economic rights, and usage of international rivers as a downstream country from an international law perspective. The methodology adopted in this thesis is a library based doctrinal legal research approach, which essentially relies on textbooks, conventions, articles, and Internet sources. The thesis concludes that the upstream countries have violated the rules of international law, particularly the principle of equitable and reasonable utilization, and participation of all countries sharing such an important resource. These countries have been using the water from these two rivers and undertake many projects without any consideration on the interests and rights of the downstream country, specifically Iraq. As a consequence, the country is suffering from lack of water problem and it negatively affects Iraq’s full potential of achieving both the economic and social development. Finally, the thesis recommends that Iraq has to work with the upstream countries on a permanent basis for better coordination and management of the two rivers, in line with the principles of international law such as the Convention on the Law of the Non-navigational Uses of International Watercourses 1997 and the bilateral agreements.